Antiamoebic Susceptibility in Acanthamoeba Keratitis: Comparison of Isolates From South India and Northern California. Issue 1 (24th January 2023) - Richardson, Quintin R.; Prajna, Lalitha; Elakkiya, Shanmugam; Kamal, Fathima Sulthana; Talbott, Maya; Prajna, Namperumalsamy Venkatesh; Rajaraman, Revathi; Cevallos, Vicky; Seitzman, Gerami D.; Lietman, Thomas M.; Keenan, Jeremy D.
Abstract : Purpose: Outcomes of Acanthamoeba keratitis are often worse in India than in the United States. The goal of this study was to determine whether antiamoebic susceptibility patterns were different when comparing Acanthamoeba isolates from India with those of the United States. Methods: Acanthamoeba isolates were obtained from corneal scrapings of 43 patients with infectious keratitis seen at the Francis I. Proctor Foundation (N = 23) and Aravind Eye Hospital (N = 20) from 2008 through 2012 and plated on growth media. A previously described minimum cysticidal concentration (MCC) assay was performed by a single laboratory technician to assess susceptibility to 5 antiamoebic agents for all isolates. Testing was conducted in triplicate, with the median MCC chosen for analyses. Results: The MCC (μg/mL) of polyhexamethylene biguanide was 6.25 [IQR 5.47–12.5] for Aravind isolates and 6.25 [IQR 6.25–9.375] for Proctor isolates ( P = 0.75), corresponding values were 6.25 [IQR 3.125–6.25] and 3.125 [IQR 3.125–9.375] for chlorhexidine ( P = 0.81), 2500 [IQR 2500–5000] and 5000 [IQR 1250–20, 000] for voriconazole ( P = 0.25), 15.6 [IQR 15.6–39.0625] and 15.6 [IQR 15.6–31.25] for hexamidine ( P = 0.92), and 15.6 [IQR 7.81–15.6] and 15.6 [IQR 7.81–31.25] for propamidine ( P = 0.42). Conclusions: This study found no statistically significant differences in antiamoebic susceptibility of Indian versus US samples from Acanthamoeba keratitis clinical isolates. These findings suggest that differences in antiamoebic susceptibility are likely not responsible for differential outcomes in Acanthamoeba keratitis between the 2 locations.